Comprehensive analysis of genes associated with necroptosis and pyroptosis in intestinal ischemia-reperfusion injury - Shuang Bao; YanBo Sun; YiChen Hu; XueFen Lei; YuanPei Zhao; WeiMing Li (PLoS ONE, 2025)
Background Intestinal ischemia–reperfusion (II/R) injury is a severe clinical condition in which regulated cell death programs—including pyroptosis and necroptosis—have emerged as key drivers of tissue damage and inflammation. We sought to delineate cell-death–related molecular signatures and candidate therapeutic targets in II/R injury. Methods We obtained transcriptome datasets from Gene Expression Omnibus (GEO) databases for mice (GSE96733, GSE232246) and humans (GSE37013). We cross-referenced genes associated with necroptosis and pyroptosis with differentially expressed genes to identify death-related features. Hub genes were identified through the topological structure of protein interaction networks and validated using an internal validation set, an independent validation set, WGCNA, and qRT-PCR. These genes were also associated with immune cell infiltration. Drug–gene interactions were predicted using DGIdb and verified through molecular docking. Results We identified 1,027 differentially expressed genes (DEGs) in the training set and derived 7 cell death-related differentially expressed genes (DCDEGs) by intersecting gene sets associated with necroptosis and pyroptosis. PPI-based prioritization identified four hub genes— Il1 β, Ripk3, Sting1 (Tmem173), and Tnfaip3 —suggesting cross-regulatory interactions between inflammation and cell death in ischemia-reperfusion pathology. These hub genes were validated using WGCNA analysis and an internal validation set. Immune infiltration analysis indicated significant correlations between hub genes and multiple immune compartments. A predictive model showed good discrimination in the discovery data, and 54 candidate drugs targeting the hub genes were retrieved. qRT-PCR confirmed dysregulation of three hub genes. Conclusion Il1 β, Ripk3, Sting1 , and Tnaip3 were identified as hub genes associated with necroptosis and pyroptosis in intestinal ischemia-reperfusion (II/R) injury. This study provides a reproducible framework and identifies testable targets for translational exploration.